The second International Symposium on Networked Learner Support - Sarah Ashton (Information Research: An International Electronic Journal)
The theme of this year's event was 'New services, roles and partnerships for the on-line learning environment'. The Symposium focused on the potential of computer-mediated communications (CMC) and the Web in the provision of information support, and on the organisational and professional development issues associated with the NLS role. It aimed to offer an opportunity for those involved in creating networked learning resources and developing on-line information support strategies to share experience and ideas, and to contribute to developing good practice in this new area of activity